FACIAL EXPRESSIONS IN NONVERBAL COMMUNICATION ("Conference on Universal Science Research 2023", 2023)
This article explores the role of facial expressions in nonverbal communication. Facial expressions are a crucial component of nonverbal communication, as they convey a wide range of emotions and attitudes that can greatly enhance our ability to understand and connect with others. The article reviews recent research on facial expressions, including the universality of facial expressions across cultures, the role of facial expressions in conveying emotions and attitudes, and the importance of context in interpreting facial expressions. The article also discusses the potential implications of facial expressions for interpersonal communication, including their use in building rapport and establishing trust. Overall, the article highlights the importance of facial expressions in nonverbal communication and underscores the need for individuals to develop strong skills in interpreting and using facial expressions effectively in their interactions with others.